Pengaruh Auditor Internal, Pengendalian Internal, dan Implementasi Good Corporate Governance terhadap Pencegahan Fraud - Fatmawati; Muhammad Ashari; Ade Ikhlas Amal Alam (Accounting Department, Faculty of Economics and Business, Universitas Hasanuddin, 2024)
This research aims to examine and analyze the influence of internal auditors, internal controls, and the implementation of good corporate governance on fraud prevention. This study is a quantitative research that utilizes primary data as its source. The method used in this research is a survey method by distributing questionnaires to 77 respondents who are employees of Bank BNI Regional Office in Makassar. The hypothesis testing employed is multiple linear regression analysis. The research results indicate that internal auditors and internal controls have a positive effect on fraud prevention, while the implementation of good corporate governance has a negative effect on fraud prevention. The overall test results show that internal auditors, internal controls, and the implementation of good corporate governance have a positive effect on fraud prevention.